Exercise leads to metabolic changes associated with improved strength and fatigue in people with MS. Issue 6 (6th May 2021) - Keller, Jennifer; Zackowski, Kathleen; Kim, Sol; Chidobem, Ikechukwu; Smith, Matthew; Farhadi, Farzaneh; Bhargava, Pavan
Abstract: Objective: The goal of this exploratory study was to evaluate the effects of an exercise intervention – progressive resistance training (PRT) on the metabolome of people with MS (pwMS) and to link these to changes in clinical outcomes. Methods: 14 pwMS with EDSS <4.0 and 13 age‐ and sex‐matched healthy controls completed a 12‐week in‐person PRT exercise intervention. Outcome measures included: plasma metabolomics analysis, cardiovascular fitness tests, EDSS, timed 25‐foot walk (T25FW), six‐minute walk test (6MWT), hip strength, and modified fatigue impact scale (MFIS). We identified changes in the metabolome with PRT intervention in both groups using individual metabolite abundance and weighted correlation network defined metabolite module eigenvalues and then examined correlations in changes in metabolite modules with changes in various clinical outcomes. Results: In both groups PRT intervention improved hip strength, distance walked in 6WMT, speed of walking, while fatigue (MFIS) was improved in pwMS. Fatty acid, phospholipid, and sex steroid metabolism were significantly altered by PRT in pwMS but not in controls. Changes in fatigue (MFIS score) were strongly inversely correlated and hip strength was moderately correlated with change in sex steroid metabolite module in pwMS. A similar relationship was noted between change in dehydroepiandrosterone sulfate abundance (sex steroid metabolite) and fatigue in pwMS. We also noted an inverse correlation between changes in fatty acid metabolism and cardiovascular fitness in pwMS. Interpretation: PRT‐induced metabolic changes may underlie improved clinical parameters in pwMS and may warrant investigation as potential therapeutic targets in future studies.